Immunization during COVID-19: let the ninja dance with the dragon - Sanjeev Singh; Sruti Singha Roy; Kirti Sundar Sahu (College of Public Health Sciences, Chulalongkorn University, 2021)
Purpose - Throughout history, pandemics have played a significant role in reshaping human civilizations through mortalities, morbidities, economic losses and other catastrophic consequences. The present COVID-19 pandemic has brought the world to its knees resulting in overstretched healthcare systems, increased health inequalities and disruptions to people's right to health including life-saving routine immunization programs across the world. Design/methodology/approach - This is a commentary paper. Findings - Immunization remains one of the most successful, safe, cost-effective and proven fundamental disease prevention measures in the history of public health. However, the COVID-19 pandemic has effectively thrown the world's immunization practices out of gear, depriving approximately 80 million infants, in rich and poor countries alike, at risk of triggering a resurgence of vaccine-preventable diseases such as diphtheria, measles and polio. It is estimated that each COVID-19 death averted by suspending immunization sessions in Africa could lead to 29-347 future deaths due to other diseases including measles, yellow fever, polio, meningitis, pneumonia and diarrhoea. Originality/value - The value of implementing robust immunization policies cannot be underestimated. Risks associated with postponing immunization services and the fact that COVID-19 is now an integral part of human civilization have resulted in several countries making special efforts to continue their immunization services. However, critical precautionary measures are warranted to prevent COVID-19 among healthcare service providers, facilitators, caregivers and children during the immunization sessions.